Feeling Psychological Alienation and its relation with Internet using among Zakho university students. - mohammed, Zahid S.; Omar, Jihan H. (Humanities Journal of University of Zakho, 2017)
The study aimed to introduce feeling psychological alienation and internet using among Zakho university students, according to gender, classes , department , by applied scale of psychological alienation feeling and practicing related questionnaires on a sample of(157) students from different classes and department , after using relevant statistical formula, and gained that there is a feeling psychological alienation almost (15.44%), while(84.56%) of them don't feel it. The result showed that almost ( 92% ) from the over-all member of sample using internet, also showed that there is a parallel relationship between those who use internet by any tools, who using for more than three hours per a day and those who use it for non-public social relations, those who use it for entertainment, athletic, scientific purposes and its psychological alienation feeling. Results, also showed that using internet doesn't causes to improvement psychological alienation toward members of family, friends and folk. From other side (45% - 65%) of those who feel psychological alienation by using internet don't feel improvement in the level of family, friends and folk's acceptance. While nearly(40%) of those who feel psychological alienation believed that using internet by them effected on their abiding by social rules, as well as about(30%) of them feel that caring about others emotions decreased. Furthermore nearly(25%) of them feel that level of cooperating with others has been decreased. In addition to about( 30% ) feel that their social responsibility towards other have been decreased . Besides about(50%) them feel that after using internet their social activities have been decreased in the society.